1991
DOI: 10.1063/1.106046
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic acceptor antisite defects in GaAs under hydrostatic pressure

Abstract: Photoluminescence is used to study the behavior of CAs-related and GaAs cation antisite defect centers in GaAs under hydrostatic pressure at 10 K. The pressure coefficients, α, for these transitions were determined. We found α(CAs) to be about 12 meV/kbar which is very close to the band edge pressure dependence. The GaAs center demonstrated only slightly smaller coefficient. This makes the binding energy of CAs and GaAs, at 26 and 77 meV, respectively, almost independent of pressure. At pressures above 30 kbar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
1

Year Published

1994
1994
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
5
1
Order By: Relevance
“…15 and 16͒ spectra in diamond-anvil cells. Due to the technological importance of GaAs, the DIT was used to investigate various aspects of band-structure theory including the scattering cross sections of intraband transitions, 1,2 the formation of shallow impurities, [17][18][19] the nature and origin of the DX center, [20][21][22] and the dynamics of excited carriers. 23,24 Application of hydrostatic pressure to a cubic crystal causes the volume to decrease while preserving the crystal symmetry.…”
mentioning
confidence: 99%
“…15 and 16͒ spectra in diamond-anvil cells. Due to the technological importance of GaAs, the DIT was used to investigate various aspects of band-structure theory including the scattering cross sections of intraband transitions, 1,2 the formation of shallow impurities, [17][18][19] the nature and origin of the DX center, [20][21][22] and the dynamics of excited carriers. 23,24 Application of hydrostatic pressure to a cubic crystal causes the volume to decrease while preserving the crystal symmetry.…”
mentioning
confidence: 99%
“…The data reported by Yu and Welber (~3 GPa) 103 is considerably smaller than this value. Kangarlu et al 110 have also reported the L 6 C -X 6 C crossover at 2.5 -3.0 GPa from the photoluminescence spectra measured under hydrostatic pressure. Our estimated L 6 C -X 6 C crossover pressure (-2.8 GPa) is in good agreement with this result (see Fig.…”
Section: Pressurementioning
confidence: 91%
“…The spin-orbit splitoff hole band (r 7 v ) is twofold spin degenerate at point T, and it splits as |k| 3 to lowest order in all but the [111] and [100] directions where it remains degenerate. The s-like T 6 C conduction band also splits as |k| 3 for k in die [110] direction.…”
Section: K(w) W(w) Uamentioning
confidence: 99%
See 2 more Smart Citations